A Survey of Machine Learning Innovations in Ambulance Services: Allocation, Routing, and Demand Estimation - Reem Tluli; Ahmed Badawy; Saeed Salem; Mahmoud Barhamgi; Amr Mohamed (IEEE Open Journal of Intelligent Transportation Systems)
In the realm of Emergency Medical Services (EMS), the integration of Machine Learning (ML) techniques has emerged as a catalyst for revolutionizing ambulance operations. ML algorithms could play a pivotal role in dynamically allocating resources, devising efficient routes, and predicting demand patterns. By thoroughly reviewing the existing literature and methodologies, this paper provides a comprehensive overview of the approaches used in ambulance allocation, routing, demand estimation and simulation models. We discuss the challenges faced by these methods, emphasizing the need for innovative solutions that can adapt to real-time data and changing emergency patterns. Through this survey, we aim to offer valuable insights into the current state of research and practices, shedding light on potential areas for future exploration and development. The findings presented in this paper serve as a foundation for researchers and practitioners working towards enhancing the efficiency of ambulance deployment in EMS.